Genetic Diversity and Evaluation of Agro-Morphological Traits in Lettuce Core Collection - Suyun Moon; Onsook Hur; Seong-Hoon Kim; Yoonjung Lee; Hyeonseok Oh; Jungyoon Yi; Ho-Cheol Ko; Hee-Jong Woo; Nayoung Ro; Young-Wang Na (Plants, 2024)
Lettuce (Lactuca sativa) is a globally significant leafy vegetable, valued for both its economic and nutritional contributions. The efficient conservation and use of the lettuce germplasm are crucial for breeding and genetic improvement. This study examined the genetic diversity and population structure of a core collection of the lettuce germplasm using genotyping by sequencing (GBS). A total of 7136 high-quality single-nucleotide polymorphisms (SNPs) were identified across nine chromosomes. Population analysis through Bayesian clustering and discriminant analysis of principal components (DAPC) revealed three distinct genetic clusters. Cluster 2 exhibited the greatest genetic diversity (He = 0.29, I = 0.44), while Cluster 3 had high levels of inbreeding (F = 0.79). Agro-morphological trait evaluation further identified significant differences in leaf length, plant weight, and head height across clusters. These findings provide valuable insights into the genetic and phenotypic diversity of lettuce, facilitating the development of more robust breeding programs. Additionally, the core collection established in this study offers a representative subset of the lettuce germplasm for future genomic research and conservation efforts.